DNA structure influences sequence specific cleavage by bleomycin. - Nightingale, K P (1993)
We have examined the cleavage of several synthetic DNA sequences by iron(II)-bleomycin. We find that, although bleomycin cuts mixed sequence DNAs with a preference for GC = GT > GA >> GG, it efficiently cleaves regions of (AT)n cutting exclusively at ApT, not TpA. Isolated ApT steps show very little cleavage while blocks of three or more contiguous ATs are cut as efficiently as GpT. This cleavage is specific for (AT)n, since sequences of the type (TAA)n.(TTA)n and (ATT)n.(AAT)n are hardly cut at all. No cleavage is observed at ApC or CpA within sequences of the type (AC)n.(GT)n; regions of An.Tn are also not cut. Although the cobalt-bleomycin complex (which binds to but does not cleave DNA) yields good DNase I footprints at GT and GC sites, no footprints are observed within (AT)n, suggesting that although the cleavage reaction is efficient, the binding affinity is relatively weak. We propose a model in which bleomycin cleavage is determined by local DNA structure, while strong binding requires the presence of a guanine residue.